Synthesis of Eco Enzyme as a Technology for Making Biodegradable Detergent Moringa Leaves (Moringa oleifera) in Supporting Green Antibacterial Products - Sulfa, Devi Mariya; Anggarani, Dinar Arsy Arsy; Susanto, Hendra; Daniarsih, Ajeng (Universitas Al Azhar Indonesia, 2024)
The organic waste from plants is currently increasing and has not been optimally processed. One of the solutions to save the earth from waste by processed the organic waste into eco enzymes. Eco enzyme is processed through fermentation of a mixture of leftover organic waste which can be used in the manufacture of biodegradable detergents. The manufacture of biodegradable detergents requires natural surfactants as materials that are safe for the environment and humans to replace the chemical compounds. Moringa leaves contain saponins as surfactants which have function as antibacterial and antioxidants. The purpose of this research is to produce biodegradable detergents which are processed through the synthesis eco enzymes and mix the moringa leaf surfactants, as well as to determine the antibacterial compounds found in biodegradable detergent. The method used is experimental research. Detergent biosurfactant is obtained from the process of maceration and evaporation of moringa leaves. The result of mixing detergent with eco enzyme is light brown color, has a distinctive fruity scent, and has a pH value of 10. The liquid detergent produced is according to SNI standard with strong antibacterial power. The results showed that biodegradable detergent can effectively remove bacteria and stains on clothes.Keywords— Liquid detergent, Eco enzyme, evaporation, fermentation